Serum laminin, type IV collagen and hyaluronan as fibrosis markers in non-alcoholic fatty liver disease - Santos,V.N. dos (2005)
Hepatic fibrosis in patients with non-alcoholic fatty liver disease is associated with progression of the disease. In the present study, we analyzed the discriminative ability of serum laminin, type IV collagen and hyaluronan levels to predict the presence of fibrosis in these patients. In this preliminary report, we studied 30 overweight patients divided into two groups according to the absence (group I, N = 19) or presence (group II, N = 11) of fibrosis in a liver biopsy. Triglycerides, aspartate aminotransferase, alanine aminotransferase, gamma-glutamyltranspeptidade, hyaluronan (noncompetitive fluoroassay), type IV collagen, and laminin (ELISA) were determined. Group II presented significantly higher mean laminin, hyaluronan, type IV collagen, and aspartate aminotransferase values, which were due to the correlation between these parameters and the stage of fibrosis in the biopsy (Spearman's correlation coefficient, rS = 0.65, 0.62, 0.53, and 0.49, respectively). Analysis of the ROC curve showed that laminin values >282 ng/ml were those with the best diagnostic performance, with 87% accuracy. Association of laminin with type IV collagen showed improvement in the positive predictive value (100%), but with reduction in diagnostic sensitivity (64%). When compared with the criteria of Ratziu et al. [Gastroenterology (2000) 118: 1117-1123] for the diagnosis of septal fibrosis, laminin values presented a better diagnostic accuracy (83 vs 70%). Determination of extracellular matrix components in serum, especially of laminin, may identify patients with non-alcoholic fatty liver disease and fibrosis and these components may be used as indicators for liver biopsy in these patients.